Collodi, Edizione Nazionale delle Opere di Carlo Lorenzini, Volume II (ENTHYMEMA, 2011)
Review of the second volume of Collodi. Edizione Nazionale delle Opere. ed. by Carlo Lorenzini. Firenze: Giunti, 2010, with a Preface by Ernesto Ferrero and an Introduction by Renato Bertacchini. The volume includes Macchiette, a collection of stories written by Collodi over twenty years. Through the examination of the most important aspects of this volume and with several references to the first volume, this review will provide the reader with new elements for enriching the profile of a writer who has marked the history of Italian literature with some new insights.